2004
DOI: 10.1096/fj.03-0839fje
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin, a natural product of heme catabolism, induces tolerance to cardiac allografts

Abstract: Biliverdin, a product of heme oxygenase-1 (HO-1) enzymatic action, is converted into bilirubin, which has been considered a waste product in the past. We now show that administration of biliverdin has a salutary effect in organ transplantation. A brief course of treatment with biliverdin leads to long-term survival of H-2 incompatible heart allografts. Furthermore, those recipients harboring long-surviving (>100 days) allografts were tolerant to donor antigens indicated by the acceptance of second donor strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
155
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(158 citation statements)
references
References 36 publications
1
155
0
2
Order By: Relevance
“…We assume that it is the effect of increased bilirubin/biliverdin, as in Gunn rats or rats carotid arteries treated with biliverdin, on VSMC cell cycle progression that suppresses neointimal proliferation after balloon injury, as reagents inhibiting cell cycle progression in VSMCs do have antiatherosclerotic properties. 1,2 We cannot rule out that at least in part the anti-inflammatory 32,33 and/or immunosuppressive 34,35 properties that have been attributed to bilirubin/biliverdin may contribute to our observations.…”
Section: Discussionmentioning
confidence: 83%
“…We assume that it is the effect of increased bilirubin/biliverdin, as in Gunn rats or rats carotid arteries treated with biliverdin, on VSMC cell cycle progression that suppresses neointimal proliferation after balloon injury, as reagents inhibiting cell cycle progression in VSMCs do have antiatherosclerotic properties. 1,2 We cannot rule out that at least in part the anti-inflammatory 32,33 and/or immunosuppressive 34,35 properties that have been attributed to bilirubin/biliverdin may contribute to our observations.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that IL-2 can play an antiinflammatory role during early phases of CIA induction, but is proinflammatory in established disease (32). Previous studies have demonstrated that carbon monoxide inhibits T cell proliferation and IL-2 secretion (33), and biliverdin has been shown to inhibit IL-2 transcription and T cell proliferation in a murine model of heart transplantation (15). Our results in established CIA support the concept that HO-1 activity could exert immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained [5,6,8,11,12,14,15(N)-3 H]-prostaglandin E 2 (PGE 2 ) from Amersham Biosciences (Barcelona, Spain). Cyclooxygenase 2 (COX-2)-specific polyclonal antibody was purchased from Cayman Chemical (Ann Arbor, MI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that treatment with biliverdin enhances tolerance of cardiac allografts, and that this tolerance is mediated by inhibition of the transcription factors NFAT and NF-jB. 61 As a clinically relevant example, it has been reported that low levels of bilirubin correlate with an increased incidence of inflammatory coronary artery disease. 62 Conversely, a genetic predisposition of persons with moderately increased levels of bilirubin, as is observed in Gilbert syndrome, significantly reduces the incidence.…”
Section: Discussionmentioning
confidence: 99%